Dust properties around NGC 7023 nebula in interstellar medium using IRIS, AKARI, and WISE survery - Subedi, Anil; Chaudhary, Ashok; Chaudhary, Keshab; Khatiwada, Kushal; Kandel, Ramchandra; Narayan Yadav, Shiv; Raj Upadhyay, Devendra; Kumar Jha, Ajay (Himalayan Physics, 2023)
We have studied the physical properties of dust around the nebula NGC 7023. The physical properties have been studied at 60 μm and 100 μm in the IRIS survey, 90 μm and 140 μm in the AKARI survey, and 12 μm and 22 μm in the WISE survey at the right ascension (R.A.) (J2000) = 21h01m35.60s, declination (J2000) = + 68o10m10.0s. The nebula is found at a distance of 335.82 pc from us. We found the dust color temperature is in the range between 36.19 K ± 0.03 K to 24.49 K ± 0.03 K with an average dust color temperature of 28.24 K ± 0.03 K in IRIS survey and a range between 38.80 K ± 0.25 K to 21.00 K ± 0.25 K with an average dust color temperature 26.39 K ± 0.25 K in AKARI survey. Similarly, in WISE, the dust color temperature was found in the range between 130.92 K ± 0.01 K to 88.71 K ± 0.01 K with an average of 104.76 K ± 0.25 K. The temperature in WISE is higher than that of the IRIS and AKARI survey. We have also calculated the dust mass, whose average value was found to be 1.18 x 1027 kg (5.93 x 10−4 M⊙) in IRIS, 1.06 x 1028 kg (5.33 x 10−3 M⊙) in AKARI, and 1.06 x 1027 kg (5.33 x 10−4 M⊙) in the WISE survey. We have also studied the visual extinction parameter due to such dust in infrared bands. This work will contribute to understanding infrared band emission from the dusty region around the nebular structure in the interstellar medium.